Modern labor economics : theory and public policy - Smith, Robert Stewart; Ehrenberg, Ronald G; Hallock, Kevin F., 1969- (Routledge, 2023)
"Modern Labor Economics: Theory and Public Policy, now in its fourteenth edition, continues to be the leading text for one-semester courses in labor economics at the undergraduate and graduate levels. It offers a thorough overview of the modern theory of labor market behaviour and reveals how this theory is used to analyze public policy. Designed for students who may not have extensive backgrounds in economics, the text balances theoretical coverage with examples of practical applications that allow students to see concepts in action. The authors believe that showing students the social implications of the concepts discussed in the course will enhance their motivation to learn. As such, this text presents numerous examples of policy decisions that have been affected by the ever-shifting labor market. This new edition continues to offer: a balance of relevant, contemporary examples; coverage of the current economic climate; introduction to basic methodological techniques and problems; tools for review and further study. This fourteenth edition presents updated data throughout and a wealth of new examples, such as the impact of COVID-19 lockdowns, gig work, nudges, monopsony power in the technology industry, and the effect of machine learning on inequality. Supplementary materials for students and instructors are available on the book's companion website"--